Assessing Farmer Knowledge and the Effectiveness of ISPO Certification Support in Sintang Regency - Fernando, Fachrozi Arif; Maswadi, Dhimaz; Fitrianti, Wanti (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2026)
The palm oil industry in Indonesia faces problems and criticism for causing deforestation, destroying biodiversity, employing minors, and violating human rights. This problem limits access for Indonesian palm oil to the European Union. To overcome this, the ISPO (Indonesian Sustainable Palm Oil) Certification Program was established by the Indonesian government with the aim of increasing the competitiveness of Indonesian palm oil in the world market. However, there are still a limited number of independent farmers who have obtained ISPO certification. This is due to a lack of information and knowledge regarding the application of ISPO principles and criteria, as well as a lack of socialization regarding the importance of ISPO certification among independent farmers. This research aims to determine the level of knowledge and effectiveness of implementing the ISPO certification program, as well as analyze the extent to which elements of knowledge influence the effectiveness of this program. The research used a quantitative descriptive method with 87 ISPO-certified independent farmers in Sintang Regency as respondents. Data analysis was carried out using descriptive statistics and Structural Equation Modeling (SEM) using SMARTPLS 4.0 software. The research results show that the level of farmer knowledge is in the